2023
DOI: 10.1590/1413-81232023282.17842022
|View full text |Cite
|
Sign up to set email alerts
|

Vacinação contra poliomielite no Brasil de 2011 a 2021: sucessos, reveses e desafios futuros

Abstract: Resumo A queda de coberturas vacinais (CV) na infância, entre elas a da poliomielite, vem se tornando uma preocupação sanitária. O objetivo foi analisar a tendência temporal das coberturas das três doses da vacina contra a poliomielite nos primeiros 12 meses de vida entre 2011 e 2021, com destaque na pandemia de COVID-19, além de mapear as CV no Brasil. Foi realizado um estudo ecológico com técnicas de série temporal interrompida (STI) e análise espacial, a partir dos dados do Sistema de Informação do Programa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
8
Order By: Relevance
“…Vaccines stimulate the immune system, protecting one’s health and preventing disabilities and deaths from preventable diseases, such as polio, diphtheria, tetanus, whooping cough, hepatitis B, haemophilus influenza type b, measles, mumps and rubella, among others. The reduction in vaccination coverage has the potential for the emergence of epidemics and an increase in infant mortality 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccines stimulate the immune system, protecting one’s health and preventing disabilities and deaths from preventable diseases, such as polio, diphtheria, tetanus, whooping cough, hepatitis B, haemophilus influenza type b, measles, mumps and rubella, among others. The reduction in vaccination coverage has the potential for the emergence of epidemics and an increase in infant mortality 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…As vacinas estimulam o sistema imunológico, protegendo a saúde e evitando incapacidades e mortes por agravos preveníveis, como a poliomielite, difteria, tétano, coqueluche, hepatite B, haemophilus influenza tipo b, sarampo, caxumba e rubéola, entre outras. A redução das coberturas vacinais tem potencial para a emersão de epidemias e aumento da mortalidade infantil 33 , 34 .…”
Section: Discussionunclassified
“…It should be noted that the main and most worrying consequence of the reduction in vaccination coverage is the reemergence of vaccine-preventable diseases that were once eradicated (Donalisio et al, 2023). As an example, mention is made of the yellow fever epidemic that occurred in Brazil between the years 2016-2019, with a record of more than 2,200 cases of infected people and a total of more than 750 deaths between December 2016 and the month June 2019 (Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate our study since, when analyzing only 2017, the highest PAs were for the Pentavalent (20.9%) and Poliomyelitis (19.6%) vaccines, followed by the Oral Human Rotavirus (16.4%) vaccine. Using Brazil national data, Donalísio et al 47 also identified high abandonment rates for the poliomyelitis vaccine, especially in the North and Northeast regions.…”
Section: Discussionmentioning
confidence: 99%